RISIKO HIPERTENSI PADA PEREMPUAN DILIHAT DARI AKTIVITAS FISIK DAN STRES DI PUSKESMAS KASEMEN SERANG BANTEN - Rezky Ariska Amnor; Dian Mediana (Fakultas Kedokteran Universitas Trisakti, 2025)
Background: Hypertension is always increasing every time, estimated to 1.5 billion individuals will be infected by 2025. Hypertension is a disease caused by many factors. Women of menopause have a greater risk of developing hypertension. It is also associated with a lack of physical activity, exerting a significant influence on blood pressure. In addition, continuous stress is also a factor causing hypertension. Methods: This study was conducted on 100 respondents in September - December 2023 at Puskesmas Kasemen, Serang, Banten using an analytics observational method with a non random consecutive sampling technique. Data processing using cross sectional methods with Fisher test. The data was obtained using questionnaires about physical activity and stress levels, and a sfigmomanometer. Results: The distribution of respondents with pre-elderly age was 54 people (54%), less physical activity was 60 people (60%), and severe stress was 55 people (55%). In the case of hypertension, 54 people (54%) suffered grade II hypertension, and more were uncontrolled (59%). There was no significant relationship between age, physical activity, and stress with controlled hypertension (p=0.220; 0.402; 0.762). There was no significant relationship between age and physical activity with uncontrolled hypertension (p=0.136; 0.440). While there was a relationship between stress and uncontrolled hypertension (p-0.000). Conclusion: There was no significant relationship between age and physical activity with controlled and uncontrolled hypertension in elderly women. Stress was not significantly related to controlled hypertension, but significantly related to uncontrolled hypertension in elderly women.